MSMEs Answer the Challenges of Digitalization - Nuri Kartini; Muhammad Nana Trisolvena; Budi Susanto; Harry Gunawan (Jurnal Abdisci, 2024)
The Cirebon City Cooperative Office organized this community service activity on MSMEs Responding to the Challenges of Digitalization in collaboration with Radio Republik Indonesia Cirebon City. The participants who attended were MSME actors in Cirebon City. The material presented in this counseling is the development of Industry 1.0 to 4.0 technology and the disruption of information technology, which requires MSME players to be digitally literate so that their businesses can develop under the demands of the times. The challenges and benefits of digital technology are delivered. The steps that need to be taken are determining the target market, preparing superior products, preparing payment models, preparing delivery models, and starting sales with digital marketing. The results of the activities organized by the Cirebon City Cooperative Office and RRI Cirebon City received support and positive responses from the participants when they saw the presence of MSMEs and so many questions asked by the participants. The existence of this collaboration is expected in the future. The digitization process of MSMEs in Cirebon City can run smoothly, and it can increase the welfare and income of MSMEs.